(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Depression and fatigue are frequent but underrecognized complications of stroke, particularly in low- and middle-income countries. Evidence from Central Asia is scarce. Objective To assess the prevalence and severity of depression and fatigue, and their associations with mental well-being among first-time and recurrent stroke survivors in Kazakhstan. Methods We conducted a cross-sectional study of 150 stroke survivors (127 first-ever, 23 recurrent) treated at a multidisciplinary hospital in Aktobe, Kazakhstan (February–July 2024). Depression, fatigue, and mental well-being were assessed using the Beck Depression Inventory-II (BDI-II), the Fatigue Assessment Scale (FAS), and the Mental Health Continuum–Short Form (MHC-SF). Group comparisons used chi-square tests, t-tests. Multivariable logistic regression models estimated adjusted odds ratios (AOR) with 95% confidence intervals (CI). Results Overall, 50.7% of patients reported depressive symptoms and 54.7% had clinically significant fatigue. Recurrent stroke survivors demonstrated higher depression scores than firstever stroke patients (BDI-II: 15.0 ± 6.98 vs. 9.97 ± 7.99; p = 0.001). Fatigue and mental well-being did not differ significantly between groups. Regression analysis confirmed an independent association between recurrent stroke and depression (AOR = 0.30; 95% CI: 0.13–0.72). Depression and fatigue were moderately correlated (r = 0.45) and both were inversely correlated with mental well-being. Conclusions Depression is significantly more common among recurrent stroke survivors, while fatigue is highly prevalent regardless of stroke history. Integrated rehabilitation in Kazakhstan should include systematic screening and psychological support to address these complications. BJMS, Vol. 25 No. 01 January’26 Page : 343-352